Licensing Biotech Intellectual Property in University–Industry Partnerships - Drozdoff, Vladimir (Cold Spring Harb Perspect Med, 2015)
Appropriate negotiation and drafting of license agreements are critical to successfully establishing and managing the expansive and complex relationships that are becoming more common between industry and universities. More often than not, the resulting licensing agreements become quite lengthy and complex, and the key principles become difficult to discern among all the details. This summary provides a short, nonexhaustive introduction to some of the essential components of these licenses with the intent of providing the non–licensing professional a better appreciation of some of the key commercial and legal terms from both an academic and company perspective, keeping in mind some of the considerations that particularly apply to biotechnology deals.